A re-sequencing-based ultra-dense genetic map reveals a gummy stem blight resistance-associated gene in Cucumis melo. (7th September 2017) - Hu, Zhongyuan; Deng, Guancong; Mou, Haipeng; Xu, Yuhui; Chen, Li; Yang, Jinghua; Zhang, Mingfang
Abstract: The melon ( Cucumis melo ) genome and genetic maps with hundreds to thousands of single nucleotide polymorphism markers were recently released. However, a high-resolution genetic map was lacking. Gummy stem blight (Gsb) is a destructive disease responsible for considerable economic losses during melon production. We herein describe the development of an ultra-dense genetic map consisting of 12, 932 recombination bin markers covering 1, 818 cM, with an average distance of 0.17 cM between adjacent tags. A comparison of the genetic maps for melon, watermelon, and cucumber revealed chromosome-level syntenic relationships and recombination events among the three Cucurbitaceae species. Our genetic map was useful for re-anchoring the genome scaffolds of melon. More than 92% assembly was anchored to 12 pseudo-chromosomes and 90% of them were oriented. Furthermore, 1, 135 recombination hotspots revealed an unbalanced recombination rate across the melon genome. Genetic analyses of the Gsb-resistant and -susceptible lines indicated the resistance phenotype is mediated by a single dominant gene. We identified Gsb-resistance gene candidates in a 108-kb region on pseudo-chromosome 4. Our findings verify the utility of an ultra-dense genetic map for mapping a gene of interest, and for identifying new disease resistant genes.